SWAN LAKE : QUEST FOR THE KINGDOMS - Terciero, Rey; Kearney, Megan, 1986-; Carter, Meaghan (New York, NY : Harper Alley, an imprint of HarperCollins Publishers, 2022)
Odette and Dillie are supposed to be enemies. Their kingdoms have been feuding since before they were born. But when the two princesses meet each other at the lake that separates their castles, it's clear they were destined to be best friends. Odette--who lives with a curse that magically transforms her into a swan when the sun rises--is happy to find someone who treats her like everyone else. And Dillie has finally met someone who understands her dream of having an adventure instead of sitting on a throne. When they discover that Odette's curse is the reason for tension between their families, they decide to follow an ancient legend that could lead them to someone who can set everything right. As they travel through enchanted lands, meet new allies, and fight terrible foes, Odette and Dillie are put to the ultimate test
Keywords: Princesses -- Comic books, strips, etc; Swans -- Comic books, strips, etc; Vendetta -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Fantasy comics; Graphic novels